Quality assessment of routine antenatal care services provided at a primary healthcare facility in a rural area of Delhi, India: A record-based study - Priya Kataria; Madhu K. Upadhyay; Karuna Arya; Naresh Kumar (Journal of Family Medicine and Primary Care, 2025)
Background: Antenatal care (ANC) can be defined as the care provided by skilled health-care professionals to pregnant women in order to ensure the best health outcomes. Good quality routine antenatal care forms the foundation of positive pregnancy experience. The primary care facilities play a significant role in improving antenatal care in peripheral areas. Methods: The primary objective of this study was to assess the quality of ANC provided to pregnant women at a primary health care facility in a rural area of Delhi. Available previous records from 1st of July 2019 to 30th of June 2023 were analysed. Quality assessment was done using a scoring tool, Antenatal Care Quality Assessment Tool (with a score range from 1-42). Statistical analysis was done using R studio. Results: Records of 611 women were analysed. The overall mean score of ANC-QAT in our study was 18.97 (SD = 6.02). 28% of the women received poor quality ANC (score ≤ 15), 55.5% received satisfactory quality ANC (score 16–25), and 16.5% received good quality ANC (score ≥ 26). Chi-square results showed that the women who belonged to a joint family, those who had education till high school or above, and those with a history of previous complications were more likely to have four or more ANC visits as compared to their counterpart. Conclusion: The majority of the women received satisfactory or good quality antenatal care. However, there is a scope for improvement in certain areas such as the number of ANC visits, blood investigations, deworming, and record keeping.